USE OF INFORMATION TECHNOLOGY IN THE FIELD OF EDUCATION AND CULTURE TO MAINTAIN THE QUALITY OF EDUCATION IN A MODERN SOCIETY - Juratbek Abduraimov (European Science Publishing, 2024)
This article analyzes professional competence, qualification requirements for modern specialists, effective use of methods and tools aimed at forming their professional competence in the process of training informatics and information technology teachers.
Keywords: Competence, professional competence, modern specialist, Insert method, traditional lesson, professional training, professional activity.